Influence of Nitrogen Dose and Application Method On Growth and Yield of Baby Corn (Bangladesh Agronomy Journal, 2022)
The experiment was conducted at Sher-e-Bangla Agricultural University during Rabi season of 2019-20 to find out the influence of nitrogen management on cob yield of baby corn. The experiment was laid out in a Split-plot design having 3 replications where four nitrogen dose viz., i) 0 kg N ha-1 (N1), ii) 100 kg N ha-1 (N2), iii) 150 kg N ha-1 (N3) and ii) 200 kg N ha-1 (N4) in the main plot and three nitrogenous fertilizer application method viz., i) Basal (M1), ii) side dressing at 30 DAS (M2) and iii) 50% basal + 50% side dressing at 30 DAS (M3) in the sub-plot. Almost all the studied parameters were found statistically significant. The higher plant height, dry matter plant-1, number of cobs plant-1, fresh weight cob-1, husk weight cob-1 and cob yield were observed in application of 200 kg Nha-1. Basal application of nitrogen fertilizer gave the highest cob weight and husk weight. Basal application of 200 kg N ha-1 showed the highest plant height (177.80 cm), cobs plant-1 (2.91), cob length (9.94 cm), fresh cob weight (61.05 g), de-husked cob weight (11.74 g) and husk fresh weight (49.30 g) but the highest number of cobs ha-1 (218497) from N2M3 (100 kg Nha-1 applied 50% as basal dose and 50% at 30 DAS) and highest cob yield (7732.41 kg ha-1) from N4M2 (application of 200 kg Nha-1 at 30 DAS).Bangladesh Agron. J. 2021, 24(2): 83-90